Tinjauan Rencana Adopsi IAS 41 pada Perusahaan Agrikultur di Bursa Efek Indonesia - Kurniawati, Heny (Bina Nusantara University, 2013)
The purpose of this study is to analyze the adoption plan of IAS 41 Agriculture as a part of IFRS Convergence in Indonesia by investigating the characteristics of biological assets and agriculture produce in public listed companies in Bursa Efek Indonesia (BEI). The methodology used in this study is qualitative approach by investigating financial statements of agricultural public listed companies for the year 2011. Thestudy shows that the biological assets recorded in the public listed companies range from consumable biological assets and bearer biological assets. It also shows that many bearer biological assets need more than one reporting period to be ready to produce other biological assets or agriculture produce to be harvest. According to IAS 41, these biological assets should be recorded using fair value model, however this model will not be appropriate. This findings lead to another questions what is the valuation appropriate for biological assets which have different characteristics.